Changes in plant flammability‐related traits to fire regime characteristics and biomass conditions in the Cerrado - Zanzarini, Vagner [UNESP]; Rossatto, Davi R. [UNESP]; Fidelis, Alessandra [UNESP] (Wiley, 2025)
PREMISE: Flammability-related traits in open savanna plant communities may shift in response to fire frequency (high vs. low) and history (recently vs. fire exclusion). Dead biomass accumulation and moisture content are expected to drive flammability components (combustibility and consumability). We hypothesized that in low fire frequency and fire exclusion areas, dead biomass accumulates, prolonging combustion duration with higher maximum temperatures and biomass consumption. Conversely, greater biomass should enhance combustibility, while higher moisture should dampen it. METHODS: In Cerrado open savannas, we selected areas with high or low fire frequency and areas that were recently burned or excluded from fire for the last 21 years. For grasses, forbs, and shrubs, we measured the following flammability-related traits: moisture content, dead biomass, burn rate, maximum fire temperature, and burned biomass. RESULTS: Dead biomass remained similar between fire frequencies and histories. Plants burned slowly (~0.5 cm s-1) in areas where fire frequency was low or excluded. In all areas, ca 60% of the plant biomass was consumed by fire. The percentage of initial dead biomass increased the flammability components until 75% dead biomass, but beyond this threshold, burn rate, temperature, and burned biomass declined. Moisture content consistently reduced temperature and amount of biomass burned. CONCLUSIONS: Areas with fire excluded had slower fire spread but the amount of plant biomass consumed was not substantially lower. The amount of dead biomass has nonlinear relationships with combustibility and consumability, indicating that areas with more biomass accumulation may have lower flammability. Thus, we need to investigate how flammability-related traits vary in plant communities under different fire regimes to understand fire behavior and improve management decisions.